High-Performance Non-enzymatic Glucose Sensors Based on CoNiCu Alloy Nanotubes Arrays Prepared by Electrodeposition - Gong, Xuewen; Gu, Yan; Zhang, Faqiang; Liu, Zhifu; Li, Yongxiang; Chen, Guanyu; Wang, Bo (Frontiers in Materials, 2019)
Transition metal alloys are good candidate electrodes for non-enzymatic glucose sensors due to their low cost and high performance. In this work, we reported the controllable electrodeposition of CoNiCu alloy nanotubes electrodes using anodic aluminum oxide (AAO) as template. Uniform CoNiCu alloy arrays of nanotubes about 2 μm in length and 280 nm in diameter were obtained by optimizing the electrodeposition parameters. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) measurements indicated that the as-prepared alloy nanotubes arrays are composed of 64.7 wt% Co-19.4 wt% Ni-15.9 wt% Cu. Non-enzymatic glucose sensing measurements indicated that the CoNiCu nanotubes arrays possessed a low detection limit of 0.5 μM, a high sensitivity of 791 μA mM−1 cm−2 from 50 to 1,551 μM and 322 μA mM−1 cm−2 from 1,551 to 4,050 μM. Besides, they showed high reliability with the capacity of anti-jamming. Tafel plots showed that alloying brought higher exchange current density and faster reaction speed. The high performance should be due to the synergistic effect of Co, Ni, and Cu metal elements and high surface area of nanotubes arrays.